Influence of Acarbose on Plasma Glucose Fluctuations in Insulin-Treated Patients with Type 2 Diabetes: A Pilot Study. (11th November 2015) - Li, Feng-fei; Xu, Xiao-hua; Fu, Li-yuan; Su, Xiao-fei; Wu, Jin-dan; Lu, Chun-feng; Ye, Lei; Ma, Jian-hua
Abstract : Background and Aims. To evaluate the effect of adding acarbose on glycemic excursions measured by continuous glucose monitoring system (CGMS) in patients with type 2 diabetes mellitus (T2DM) already on insulin therapy. Materials and Methods. This was an opened and unblended study. 134 patients with T2DM were recruited. After initial rapidly corrected hyperglycaemia by continuous subcutaneous insulin infusion (CSII) for 7 d, a 4–6-day premixed insulin titration period subsequently followed. Patients were then randomized 1 : 1 to acarbose plus insulin group or insulin therapy group for 2 weeks. CGMS was used to measure glucose fluctuations for at least 3 days after therapy cessation. Results . Patients in acarbose plus insulin group achieved a significant improvement of MAGE compared to that of insulin therapy only group (5.56 ± 2.16 versus7.50 ± 3.28 mmol/L, P = 0.0 44 ), accompanied by a significant decrease in the incremental AUC of plasma glucose concentration above 10.0 mmol/L (0.5[ 0.03, 0.9 ] versus 0.85[ 0.23, 1.4 ] mmol/L per day, P = 0.037 ). Conclusions . Add-on acarbose to insulin therapy further improves glucose fluctuation in patients with T2DM. This study was registered with ClinicalTrials.gov registration numberChiCTR-TRC-11001218 .